2010
DOI: 10.1177/1934578x1000500220
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of 5′-Phosphodiesterase from Barley Malt Rootlets

Abstract: Two 5'-phosphodiesterases (5'-PDE-a and 5'-PDE-b) were isolated from barley malt rootlets, and further purified by gel filtration on Sephadex G-25 and Sephadex G-75. 5'-PDE-a had a pH optimum of 5.0, temperature optimum of 70 o C, and specific activity of 0.0143 mM ⋅mg-1 ⋅min-1. 5'-PDE-b had a pH optimum of 6.0, temperature optimum of 65 o C and specific activity of 0.0125 mM ⋅mg-1 ⋅min-1. Both enzymes can be used to hydrolyze RNA to form 5'-nucleotides. The enzymes were quite stable at 70 o C for 420 minutes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…As noted in Figure 3b, the enzyme activity of 5'-PDE was favored by temperatures in the range of 60 to 70 °C. These results are in accordance with the results of Zou et al (2008) and Hua & Huang (2010), which also obtained an optimum 5'-PDE activity at temperatures in this range.…”
Section: Enzyme Characterizationsupporting
confidence: 92%
See 2 more Smart Citations
“…As noted in Figure 3b, the enzyme activity of 5'-PDE was favored by temperatures in the range of 60 to 70 °C. These results are in accordance with the results of Zou et al (2008) and Hua & Huang (2010), which also obtained an optimum 5'-PDE activity at temperatures in this range.…”
Section: Enzyme Characterizationsupporting
confidence: 92%
“…In addition, the specific activity also increased up to the maximum time studied (12h) (Figure 2f). Besides, the amount of water of the best water-rootlet ratio result (8:1) was lower in comparison to Hua & Huang (2010) results, which gives a more concentrated crude extract and reduces the cost related to enzyme concentration.…”
Section: Enzyme Extractionmentioning
confidence: 75%
See 1 more Smart Citation
“…Thus, applications of the enzyme in an industrial setting should be made at temperatures below 60°C. Hua and Huang (2010), in their recent study, found 5'-PDE from barley rootlets to be stable at 70°C for 420 minutes. On the other hand, Beluhan and Maric (2011), in their work on 5'-PDE from barley rootles, observed retention of 70% relative activity after 120 min of incubation at 70°C.…”
Section: Temperature Optimum and Stabilitymentioning
confidence: 92%
“…and cyclic guanosine monophosphate (cGMP) into their umami-tasing components, 5'-AMP and 5'-GMP, respectively. The optimum temperature for phosphodiesterases in plants is around 65°C-70°C (Hua & Huang, 2010). Therefore, during the drying process of OD120 and PR, it is possible that at the early state of drying, where temperature was not too high to inactivate the enzymes and amount of free water was sufficient for enzymatic reactions, resulting in increased 5'-AMP and 5'-GMP content, with decreased cAMP and cGMP content as shown in the heatmap (Figure 3.2B).…”
Section: Nucleotide-related Metabolitesmentioning
confidence: 99%